\require{AMSmath}

4. Quasi-symmetrische vergelijkingen

Een quasi-symmetrische vierdegraadsvergelijking heeft deze vorm:

$
ax^4  + bx^3  + cx^2  + bmx + am^2  = 0
$

Aanpak

  • deel door $x^2$
  • stap over op $\eqalign{z = x + \frac{m}{x}}$

Voorbeeld

Los op: $
x^4  - 2x^3  + 3x^2  - 2x + 1 = 0
$

Uitwerking

$
\eqalign{
  & x^4  - 2x^3  + 3x^2  - 2x + 1 = 0  \cr
  & x^2  - 2x + 3 - \frac{2}
{x} + \frac{1}
{{x^2 }} = 0  \cr
  & x^2  + \frac{1}
{{x^2 }} - 2x - \frac{2}
{x} + 3 = 0  \cr
  & x^2  + \frac{1}
{{x^2 }} + 2 - 2\left( {x + \frac{1}
{x}} \right) + 1 = 0  \cr
  & \left( {x + \frac{1}
{x}} \right)^2  - 2\left( {x + \frac{1}
{x}} \right) + 1 = 0  \cr
  & neem:z = x + \frac{1}
{x}  \cr
  & z^2  - 2z + 1 = 0  \cr
  & z = 1  \cr
  & x + \frac{1}
{x} = 1  \cr
  & x^2  - x + 1 = 0  \cr
  & x = \frac{1}
{2} - \frac{1}
{2}i\sqrt 3  \vee x = \frac{1}
{2} + \frac{1}
{2}i\sqrt 3  \cr}
$

Opgelost...


©2004-2022 WisFaq